Existence and Consistency of Theological Practice (Prayer) in the End Times - Shofiyatul Muslimah; Muhammad Ammar Al-amudi; Prabu Arya Sembara (Solo International Collaboration and Publication of Social Sciences and Humanities, 2023)
This study aims to 1) provide an explanation of the law of congregational prayer, 2) provide an explanation of the virtues of congregational prayer, and 3). Identify the factors that cause Muslims today to neglect or even abandon the Jama'ah prayer. To collect this research data, a literature research technique known as the normative juridical approach to literature evaluation was used. The Quran, the sunnah of the prophet, ijma', and qiyas are sources of information on the discussion of this congregational prayer. The findings of this study lead to the conclusion that congregational prayer is the sharia of Allah and the Messenger of Allah. The law of performing prayers in mosques, scholars of the madhab dissented.